Feeding behaviour of Patella caerulea L. and P. rustica L. under spring and neap simulated tides. An innovative approach for quick quantification of grazing activity. Issue 3 (4th May 2019) - Sempere-Valverde, Juan; Sedano, Francisco; Megina, César; García-Gómez, José C.; Espinosa, Free
Abstract : Limpets are one of the most important herbivorous grazers of temperate rocky shores, promoting diversity and influencing the structure and functioning of intertidal communities. In the current context of global change, harvesting pressures on accessible intertidal and habitat modifications caused by coastal urbanization are threatening these organisms in many coastal areas. In this regard, the improvement of ex situ maintenance techniques, combined with the understanding of limpets' behavioural traits, would help to improve the effectiveness of conservation strategies and mitigation efforts. In this study, Patella caerulea and Patella rustica grazing activity was quantified under a scenario of simulated tides. After leaving limpets to graze 10 days under two tidal amplitude regimes: Spring and Neap, radula mark coverage was obtained from the surface of wax discs with a quick image-processing methodology, using the dry-brush technique and Adobe© Photoshop and ImageJ software. Feeding activity, quantified as radula mark coverage, was higher for P. caerulea than P. rustica and, within P. caerulea, for spring over neap tides. Therefore, tidal range has to be taken into consideration when limpet specimens are maintained in captive conditions. Abstract :